2019
DOI: 10.1088/2053-1583/ab0776
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of K-excitons in multilayers of transition metal dichalcogenides

Abstract: Reflectance and magneto-reflectance experiments together with theoretical modelling based on the k · p approach have been employed to study the evolution of direct bandgap excitons in MoS2 layers with a thickness ranging from mono-to trilayer. The extra excitonic resonances observed in MoS2 multilayers emerge as a result of the hybridization of Bloch states of each sub-layer due to the interlayer coupling. The properties of such excitons in bi-and trilayers are classified by the symmetry of corresponding cryst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 59 publications
(107 reference statements)
9
56
0
1
Order By: Relevance
“…2c, d. It has been shown previously that the conduction band splitting gives rise to the spin triplet exciton, aka spin-dark exciton, in monolayer TMDCs 32,33,58 . Here, the presence of the conduction band splitting renders it possible to have two configurations of the interlayer exciton: spin triplet (IXT) and spin singlet (IXS) interlayer exciton, as shown in Fig.…”
mentioning
confidence: 91%
“…2c, d. It has been shown previously that the conduction band splitting gives rise to the spin triplet exciton, aka spin-dark exciton, in monolayer TMDCs 32,33,58 . Here, the presence of the conduction band splitting renders it possible to have two configurations of the interlayer exciton: spin triplet (IXT) and spin singlet (IXS) interlayer exciton, as shown in Fig.…”
mentioning
confidence: 91%
“…That peak can be also observed in trilayer and even multilayer MoS 2 but it cannot be as easily resolved as in the case of bilayer MoS 2 . This feature in the reflectance spectra have been recently demonstrated (through temperature dependent optical spectroscopy studies, magneto-optical measurements and density functional theory calculations) to be originated by the generation of interlayer (IL) excitons [14,15,24]. These excitons are, similarly to the A and B excitons, due to direct transitions at the K point but unlike them the electron and hole are spatially separated in the different MoS 2 layers (see the cartoon in figure 1(b)).…”
mentioning
confidence: 97%
“…Moreover, heterostructures built with these 2D systems have also attracted the interest of the scientific community because of the presence of interlayer excitons: excitons formed by electrons and holes that live in different layers [9][10][11][12][13]. Very recently, Gerber et al and Slobodeniuk et al demonstrated that naturally stacked bilayer MoS 2 (2Hpolytype) also presents interlayer excitons, with high binding energy, that can be observed at room temperature [14,15] and Niehues et al demonstrated that uniaxial strain could be used to tune the energy of the interlayer exciton [16].…”
mentioning
confidence: 99%
“…[6][7][8] Moreover, heterostructures built with these 2D systems have also attracted the interest of the scientific community because of the presence of interlayer excitons: excitons formed by electrons and holes that live in different layers. [9][10][11][12][13] Very recently, Gerber et al and Slobodeniuk et al demonstrated that naturally stacked bilayer MoS2 (2H-polytype) also presents interlayers excitons, with high binding energy, that can be observed at room temperature 14,15 and Niehues et al demonstrated that uniaxial strain could be used to tune the energy of the interlayer exciton. 16 In this work we employ biaxial strain to modify the band structure, and thus the excitonic resonances, in bilayer MoS2 flakes.…”
mentioning
confidence: 99%
“…This feature in the reflectance spectra have been recently demonstrated (through temperature dependent optical spectroscopy studies, magneto-optical measurements and density functional theory calculations) to be originated by the generation of interlayer (IL) excitons. 14,15,24 These excitons are, similarly to the A and B excitons, due to direct transitions at the K point but unlike them the electron and hole are spatially separated in the different MoS2 layers (see the cartoon in Figure 1 In order to biaxially strain the MoS2 bilayers we exploit the large thermal expansion mismatch between the PP substrate (~130×10 -6 K -1 ) and MoS2 (1.9×10 -6 K -1 ) 25 . PP has also a relatively high Young's modulus (1.5-2 GPa) for a polymer, which is essential to guarantee an optimal strain transfer from substrate to flake.…”
mentioning
confidence: 99%